2021
DOI: 10.3390/biom11081109
|View full text |Cite
|
Sign up to set email alerts
|

How Inflammation Pathways Contribute to Cell Death in Neuro-Muscular Disorders

Abstract: Neuro-muscular disorders include a variety of diseases induced by genetic mutations resulting in muscle weakness and waste, swallowing and breathing difficulties. However, muscle alterations and nerve depletions involve specific molecular and cellular mechanisms which lead to the loss of motor-nerve or skeletal-muscle function, often due to an excessive cell death. Morphological and molecular studies demonstrated that a high number of these disorders seem characterized by an upregulated apoptosis which signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 158 publications
(199 reference statements)
0
7
0
Order By: Relevance
“…While there appears to be no clear signs of muscle-intrinsic inflammatory processes, there is evidence of systemic inflammation. Reported inflammation across different tissues from SMA patients and mice (Deguise and Kothary, 2017 ; Deguise et al, 2017 ; Wan et al, 2018 ; Salucci et al, 2021 ) is suggested to aggravate atrophy of skeletal muscle and promotes cell damage. In muscle from SMA patients, smaller and disorganized myotubes are indicative of impaired growth and maturation (Martínez-Hernández et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there appears to be no clear signs of muscle-intrinsic inflammatory processes, there is evidence of systemic inflammation. Reported inflammation across different tissues from SMA patients and mice (Deguise and Kothary, 2017 ; Deguise et al, 2017 ; Wan et al, 2018 ; Salucci et al, 2021 ) is suggested to aggravate atrophy of skeletal muscle and promotes cell damage. In muscle from SMA patients, smaller and disorganized myotubes are indicative of impaired growth and maturation (Martínez-Hernández et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…SMN depletion leads to the profound loss of motor neurons of the spinal cord (Lefebvre et al, 1997 ) and peripheral organ pathology including the muscle (reviewed in Shababi et al, 2014 ). While the underlying mechanisms are not fully understood, there is growing evidence of cell death pathway activation (Simic et al, 2000 , 2007 ; Shafey et al, 2005 ; Tsai et al, 2006 , 2008 ; Dachs et al, 2011 ; Mutsaers et al, 2011 ; Hayhurst et al, 2012 ; Martínez-Hernández et al, 2013 ; Fayzullina and Martin, 2014 ; Simon et al, 2017 ; Carrasco et al, 2019 ; Courtney et al, 2019 ; Deguise et al, 2020a ; Weissman et al, 2021 ) and inflammation in several tissues in SMA (Deguise and Kothary, 2017 ; Deguise et al, 2017 ; Wan et al, 2018 ; Salucci et al, 2021 ). As such, investigating cell death mechanisms could shed light on the specific pathogenic mechanisms underlying motor neuron death and muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a number of muscular dystrophies, immune system changes are associated with increases in disease severity [ 75 ]. It is clear that inflammatory processes can lead to neuromuscular cell death thereby causing functional impairments [ 76 ]. Among the best studied changes examining this has been in Duchenne muscular dystrophy (DMD) which involves inflammatory processes which result in an imbalance in macrophage 1 and 2 phenotypes from the innate immune system [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and cellular stress responses are closely associated with motor neuron death and ALS pathology [ 29 ]. A previous study has demonstrated that abnormal changes in the immune system owing to the elevation of peripheral NKT cell levels are associated with liver pathology and disease progression in hSOD1 G93A mice [ 11 ].…”
Section: Discussionmentioning
confidence: 99%